2020
DOI: 10.1080/14756366.2020.1791842
|View full text |Cite
|
Sign up to set email alerts
|

Novel heterocyclic hybrids of pyrazole targeting dihydrofolate reductase: design, biological evaluation and in silico studies

Abstract: A novel series of pyrazole analogues including hydrazones, pyrazolo[4,3-c]-pyridazines, pyrazolo[3,4e][1,2,4]triazine and pyrazolo[3,4-d][1,2,3]triazoles was designed, synthesised and screened for their in vitro antimicrobial and DHFR inhibition activity. Compounds bearing benzenesulphonamide moiety incorporated with 3-methyl-5-oxo-1H-pyrazol-4(5H)-ylidene) hydrazine 3a or 6-amino-7-cyano-3-methyl-5H-pyrazolo[4,3-c]pyridazine 6a revealed excellent and broad spectrum antimicrobial activity comparable to ciprofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 37 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Previous in vitro enzymatic studies and computational approaches have demonstrated that molecules containing quinoline or hydrazone moieties could be very promising competitive DHFR‐TS inhibitors against protozoal species such as T. gondii and P. falciparum [26–33,40] . In addition, DHFR and TS constitute a bifunctional common and dimeric enzyme protein found ubiquitously in all dividing cells of eukaryotic organisms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous in vitro enzymatic studies and computational approaches have demonstrated that molecules containing quinoline or hydrazone moieties could be very promising competitive DHFR‐TS inhibitors against protozoal species such as T. gondii and P. falciparum [26–33,40] . In addition, DHFR and TS constitute a bifunctional common and dimeric enzyme protein found ubiquitously in all dividing cells of eukaryotic organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Previous in vitro enzymatic studies and computational approaches have demonstrated that molecules containing quinoline or hydrazone moieties could be very promising competitive DHFR-TS inhibitors against protozoal species such as T. gondii and P. falciparum. [26][27][28][29][30][31][32][33]40] In addition, DHFR and TS constitute a bifunctional common and dimeric enzyme protein found ubiquitously in all dividing cells of eukaryotic organisms. Indeed, structural alignment of the crystal structures from DHFR-TS of the protozoal species T. gondii and P. falciparum with the structure of DHFR-TS from trypanosomatidae species showed highly conserved nature around the binding site.…”
Section: Molecular Docking Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 It is emerged as a useful pharmacophore in the synthesis of potent anticancer drugs. 44,45 Moreover, multiple studies identied various thiazolyl-pyrazole compounds as potential anticancer agents. As an example, Lv and coworkers have reported that the thiazolylpyrazoline derivative I displayed potent cytotoxic activity against breast cancer cell line (MCF-7) with IC 50 of 0.07 mM via EGFR inhibition with IC 50 ; 0.06 mM.…”
Section: Introductionmentioning
confidence: 99%